(untitled) (Central Medical College Journal, 2026)
Background: Acute lower respiratory infections (ALRI) remain the major cause of morbidity and mortality among children under five years of age. Hypoxaemia is a serious complication of ALRI and represents an important risk factor for mortality. Early identification and prompt management of hypoxaemia can significantly improve outcomes in affected children. As arterial blood gas analysis is not accessible in all primary healthcare settings in developing countries, it is important to identify clinical signs that can predict hypoxemia. Objectives: To identify the clinical predictors of hypoxaemia in children with ALRI admitted to the Paediatrics ward of Chittagong Medical College Hospital (CMCH), Chattogram, Bangladesh. Materials & Methods: This hospital-based cross-sectional study included 100 children aged 2 to 60 months with ALRI admitted to the Paediatrics ward of CMCH. Demographic information, including age, sex, and place of residence, as well as presenting symptoms, were recorded for each patient. Symptoms such as cough, breathing difficulty, feeding difficulty, sleep disturbance, lethargy and clinical signs such as central cyanosis, nasal flaring, restlessness, head nodding, fast breathing, chest in drawing, grunting, crepitation’s, and rhonchi were recorded. Oxygen saturation in these children was measured using ABG analysis to identify hypoxaemia. Continuous variables were reported as mean ± standard deviation (SD), whereas categorical variables were presented as frequencies and percentages. The frequency of various symptoms and signs in both groups was calculated and analyzed using the Chi-square (χ²) test. Sensitivity, specificity, positive predictive value, and negative predictive value were determined for each symptom and sign. Statistical significance was defined as p<0.05, with a 95% confidence interval. Results: Out of 100 children, 46% had hypoxaemia as per ABG criteria (pO2 <60 mmHg). In hypoxaemic group 23 (50%) patients had feeding difficulty, 13 (28.5%) patients had cyanosis, 11 (23.9%) patients had head nodding, and 16 (34.8%) patients had grunting which has statistical significance. So, feeding difficulty, cyanosis, head nodding and grunting were single or independent significant predictors of hypoxaemia. Certain symptom combinations, especially nasal flaring with grunting, and cyanosis with nasal flaring were strongly linked to hypoxaemia with high specificity and predictive value. Restlessness with cyanosis and feeding difficulty with nasal flaring and cyanosis showed 100% specificity and positive predictive value, making these combinations reliable indicators of hypoxaemia. Conclusion: Feeding difficulty, cyanosis, head nodding and grunting were independent predictors of hypoxaemia in this study. Establishing clinical guidelines and ensuring effective oxygen delivery systems can significantly enhance treatment quality, ultimately reducing both morbidity and mortality. Central Medical College Journal Vol 9 No 2 July 2025 Page: 76-83